Analisis Motivasi Karir, Pengembangan Kompetensi, dan Penghargaan Finansial Terhadap Persepsi Minat Sertifikasi profesi Akuntansi (Studi Kasus Mahasiswa Akuntansi UPN “Veteran” Jawa Timur) - Ubbadullah, Ubbadullah; Budiwitjatsono, Gideon Setyo (Universitas Batanghari Jambi, 2024)
This study aims to examine and prove the effect of career motivation, competency development, andfinancial rewards on the perception of interest in accounting profession certification at UPN